Three dimensional P-wave velocity structure underneath the southeastern margin of the Tibetan Plateau and the deep tectonic significance. (1st April 2022) - Li, Dahu; Ding, Zhifeng; Zhan, Yan; Chang, Lijun
Graphical abstract: Highlights: A new 3-D P-wave velocity model of the upper mantle is proposed for the structure underneath the Tibetan Plateau based on the investigation of dense seismic arrays. The high-velocity anomaly below the Sichuan Basin is thinning westward, with the thickness of 350 km below eastern Sichuan Basin. A low-velocity anomaly below the Tengchong volcanic field is identified and extends to a depth of 400 km. P-wave velocity shows a high-velocity anomaly to the north of 26°N and an obvious low-velocity anomaly to the south. Abstract: The deep velocity structure underneath the southeastern margin of the Tibetan Plateau is the key to understand the tectonic evolution of the Tibetan Plateau. In this study, 145, 254 relative travel-time residuals were measured from the records of 1360 teleseismic events using the waveform correlation method, we determined the three-dimensional (3-D) P-wave velocity structures in the upper mantle using a large-scale dense seismic array. The western boundary of the Yangtze Craton extends from the Longmenshan fault zone in the north to the Red-River fault in the south, our imaging results show that in a depth range of 50–150 km, obvious differences in physical properties of the medium exist across the Longmenshan fault zone. The Red-River fault and the Xiaojiang fault are the western and eastern boundaries of Chuan-Dian diamond block, respectively. Low-velocity anomalies are visible from the north of the Red-River fault to the east of the Xiaojiang fault and their intersection region. The high-velocity anomaly below the Sichuan Basin is thinning westward, with the thickness of 350 km below eastern Sichuan Basin. We obtained a low-velocity anomaly extending 400 km below the Tengchong volcanic field. A high-velocity anomaly, extending down to the mantle transition zone, is thought to be related to the subduction of the Indian slab. Our results also reveal an obvious low-velocity anomaly exists to the south of 26°N, we speculate that the flow of the upper mantle material beneath the Tibetan Plateau affects the velocity structure in this region.